2012
DOI: 10.1021/bm300964h
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Conformational Changes for Patterning Thin Films of Recombinant Spider Silk Proteins

Abstract: Recombinant spider silk proteins mimicking the properties of dragline silk proteins represent a class of materials that hold great potential for future high-performance applications. Here we explore the self-assembly behavior of a recombinantly produced spider silk protein based on the dragline silk of the Araneus diadematus , eADF4 (C16), by selectively patterning its secondary structure using capillary transfer lithography and solvent-assisted microcontact molding. Two conformational transitions were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…We suggest that during active metabolic activity, which was not affected by the presence of the silk protein shell, partial degradation of silk occurs during exocytosis of waste products (mainly CO 2 , and ethyl alcohol) (Figure 1). Indeed, silk protein undergoes secondary structure transitions when acidity is increasing (CO 2 acts as a volatile acid) or during partial dehydration, promoting β ‐sheet content 41, 52. These peripheral reactions might promote endocytosis of degraded silk fibroin fragments, as was only observed for short protein fragments (usually 20–35 residues length) 53.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that during active metabolic activity, which was not affected by the presence of the silk protein shell, partial degradation of silk occurs during exocytosis of waste products (mainly CO 2 , and ethyl alcohol) (Figure 1). Indeed, silk protein undergoes secondary structure transitions when acidity is increasing (CO 2 acts as a volatile acid) or during partial dehydration, promoting β ‐sheet content 41, 52. These peripheral reactions might promote endocytosis of degraded silk fibroin fragments, as was only observed for short protein fragments (usually 20–35 residues length) 53.…”
Section: Resultsmentioning
confidence: 99%
“…The transition of a random silk fibroin that is soluble in water (silk I) to a highly stable and organized structure that is insoluble in water (silk II), which is required to form stable silk matrices, can be accomplished by several processing methods including dehydration by using organic solvents, surfactants, initiators or crosslinking agents, or physical factors (shear, sonication, temperature) 37–41. It also has been shown that the extent of protein aggregation can be controlled by the concentration of kosmotropic salts or ions 37.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FDCs collected in both ways contain tip sample interaction information and can be used to calculate sample mechanical properties using known tip parameters and different models of contact mechanics [35,36]. In the force-tapping mode, an AFM tip is driven sinusoidally at frequencies much lower than the cantilever's first resonant peak (typically 1 or 2 kHz) and briefly interacts with the sample surface in the middle of each cycle [37]. This measurement mode allows for the determination of various mechanical properties of the sample surface, such as elastic modulus and adhesion, as well as surface topography with high resolution in a short amount of time.…”
Section: Introductionmentioning
confidence: 99%
“…These small (D < 10 nm) semiconducting nanoparticles exhibit size-dependent broadband absorption and narrowband photoluminescence (PL) (full-width half-maximum (FWHM) below 40 nm) due to quantum confinement of the exciton. [22][23][24] In addition, the application of nanotechnology for controlled light-matter interactions has been augmented by the variety of micro-and nanoscale patterning approaches that have been developed, including techniques like electron-and photolithography, [25] soft lithographies, [26,27] inkjet printing, [28] and molding and printing. Not surprisingly, the intrinsic properties of QDs and the wide variety of QDs available have led to their implementation in a number of applications, including imaging/labeling/sensing in biological investigations, [17] light-emitting diodes (LEDs), [18] solar cells, [19,20] quantum computing, [21] and, more recently, lasers and optical gain media.…”
mentioning
confidence: 99%